An Intricate Survey on Security of Healthcare Records: Unfold Approaches, Challenges and Future Orchestration - Hamsa A S; Prakash J; Bhanushree K J (Tinta Emas Publisher, 2025)
The integration of advanced computing and wireless communication has high impact on modern healthcare systems. Today’s medical devices are capable of autonomously monitoring and managing various patient health conditions, minimizing the need for constant human oversight. Technologies such as bio implants, and the Internet of Things (IoT) are transforming the way healthcare providers track and treat patients. Striking a balance between functionality and patient privacy is crucial, as breaches in security or confidentiality can severely compromise patient care. As healthcare systems grow increasingly connected, they also become more susceptible to cyber threats, often due to design vulnerabilities and insufficient protective measures. This article delves into the range of security issues facing healthcare technologies, outlines the potential consequences of such threats, and provides a comprehensive review of known attack vectors. Additionally, it evaluates current defence strategies, highlighting their strengths and weaknesses, and proposes future research directions aimed at strengthening the security of healthcare infrastructures.